Corporate Fraud and Good Practices for its effective treatment - Isoré Gutiérrez, Felipe André (2020)
Prevention, detection, management, and response to fraud inside an organization, in any sector, must be a practice adopted by industries to avoid direct and indirect losses. This article reviews studies that present statistics and allow us to reach conclusions based on fraud cases inside companies. Fraud prevention and detection measures, corporate risk management, due diligence, corruption prevention and real cases will be explained in this article, based on public research and from the author’s viewpoint from his personal experience.